2004
DOI: 10.1002/jtr.511
|View full text |Cite
|
Sign up to set email alerts
|

Destination loyalty and repeat behaviour: an application of optimum stimulation measurement

Abstract: This paper reports on a study of consumer loyalty in the holiday destination selection process. The study does not define loyalty, but attempts to contribute to an understanding of the concept by applying a psychological measure of variety seeking directly to patterns of holiday destination choice. The measure used is based on the optimum stimulation level (OSL) concept. The guiding proposition in this study was that tourists with a high need for variety would display a varied pattern in their vacation destina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 36 publications
(39 reference statements)
4
73
0
2
Order By: Relevance
“…Moreover, a critical relationship between push/pull motivation and destination loyalty in terms of revisit intention and recommendation has been underlined by previous studies (e.g., Yoon & Uysal, 2005). In reviewing litreatures, "revisit intention" and "positive word of mouth recommendation" have been recognized as indicators of loyalty in many studies (Bigne et al, 2001;Chen & Gursoy, 2001;Niininen et al, 2004;Yoon & Uysal, 2005;Chi & Qu, 2008).…”
Section: Destination Loyaltymentioning
confidence: 96%
“…Moreover, a critical relationship between push/pull motivation and destination loyalty in terms of revisit intention and recommendation has been underlined by previous studies (e.g., Yoon & Uysal, 2005). In reviewing litreatures, "revisit intention" and "positive word of mouth recommendation" have been recognized as indicators of loyalty in many studies (Bigne et al, 2001;Chen & Gursoy, 2001;Niininen et al, 2004;Yoon & Uysal, 2005;Chi & Qu, 2008).…”
Section: Destination Loyaltymentioning
confidence: 96%
“…For example, in examining the effect of novelty seeking on tourists' return pattern to a destination, Niininen et al (2004) demonstrated that tourists with high novelty seeking tendency showed different patterns of destination choice and were less likely to return to the same destination. Assaker et al (2011) found that a higher level of novelty seeking resulted in a lower immediate intent to revisit, but a greater intent to revisit in the future.…”
Section: H5 Cruise Vacationers' Novel Experience Is Positively Assocmentioning
confidence: 98%
“…On the basis of recent tourism destination studies, it has been widely acknowledged that the intention to revisit a destination and recommended the visit to others are both signs of loyalty [2,4,5,24]. Hence, repeat visitation and recommendation to other people as well as their benefits are now widely recognized by both academics and practitioners as an important issue in tourism strategies.…”
Section: Destination and Loyaltymentioning
confidence: 99%